2009
DOI: 10.1016/j.geb.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

On the benefits of party competition

Abstract: We study the role of parties in a citizen-candidate repeated-elections model in which voters have incomplete information. We first identify a novel "party competition effect" in a setting with two opposing parties. Compared with "at large" selection of candidates, party selection makes office-holders more willing to avoid extreme ideological stands, and this benefits voters of all ideologies. We then allow for additional parties. With strategic voting, citizens benefit most when the only two parties receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…A sampling includes Barro (1973), Ferejohn (1986), Rogoff and Sibert (1988), Austen‐Smith and Banks (1989), Rogoff (1990), Banks and Sundaram (1993, 1998), Harrington (1993), Persson, Roland, and Tabellini (1997), Fearon (1999), Berganza (2000), Le Borgne and Lockwood (2001, 2006), Smart and Sturm (2003, 2007), Hindriks and Belleflamme (2005), Hatfield and Padró i Miquel (2006), Besley (2006), and Besley and Smart (2007). Exceptions are Bernhardt et al (2009), Campuzano (2005), and Meirowitz (2007).…”
mentioning
confidence: 99%
“…A sampling includes Barro (1973), Ferejohn (1986), Rogoff and Sibert (1988), Austen‐Smith and Banks (1989), Rogoff (1990), Banks and Sundaram (1993, 1998), Harrington (1993), Persson, Roland, and Tabellini (1997), Fearon (1999), Berganza (2000), Le Borgne and Lockwood (2001, 2006), Smart and Sturm (2003, 2007), Hindriks and Belleflamme (2005), Hatfield and Padró i Miquel (2006), Besley (2006), and Besley and Smart (2007). Exceptions are Bernhardt et al (2009), Campuzano (2005), and Meirowitz (2007).…”
mentioning
confidence: 99%
“…The existence of simple equilibria is proved, and it is shown that in all such equilibria, the median voter is decisive: a policy choice by an officeholder secures re-election if and only if it gives the median voter a payoff at least equal to the median's expected payoff from electing a challenger. This model has been extended to allow for term limits (Bernhardt et al 2004), for parties (Bernhardt et al 2005, Campuzano 2005, and for costly signaling in campaigns (Kang 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…characteristics. On top of that, unlike some of the previous political agency models, we do not need to consider different settings depending on whether or not the politician's characteristics are common knowledge or private knowledge (Bernhardt et al (2009) Previous literature has also looked at the role of commitment in elections. With commitment, the politician chooses the decisions that he will take while in office at the beginning of his term.…”
Section: Introductionmentioning
confidence: 99%